Structural Complexity of Early Embryos: A Study on the Nematode Caenorhabditis elegans - Bignone, F.A. (Kluwer Academic Publishers, 2001)
For analytical studies on the dynamics of gene expression, gene expressioncontrol and cellular interactions, the nematode Caenorhabditis elegans[C. elegans] is at present one of the best suited models [1–4].In this organism the genetic map and sequence is known [5], moreover theconstancy of its lineage tree allows a complete description of cellularclones giving rise to embryos. These characteristics have fostered detailedstudies on several aspects of development for this organism. Quantitativestudies of cellular movement, through time lapse cinematography of gastrulation, allows the description of cellular migrations giving rise to the final embryonic structure. In perspective, these studies coupledwith: genetic analysis, patterns of gene expression obtained throughmolecular techniques or other methods, open up the possibility of dynamicalstudies at the organismic scale. This possibility implies, first of all,a study of partitioning of space, and raise several problems in order todefine basic conceptual tools to be used in such studies. One of the mainproblems to handle in this respect is the definition of embryonic structurein a quantitative way. We will show that this aspect is a more generalcase of distance geometry approaches, as defined in protein folding studies.In this paper we discuss measures of the complexity for embryonal body plans,at the end of grastrulation. These can be applied to studies on the dynamicsof gene expression and phylogenetic studies with further experiments orsimulations.